Analisis Sosial Ekonomi dan Faktor yang Mempengaruhi Produksi Petani Kelapa Sawit di Kecamatan Merlung - Anggun, Deby; Irawan, Deki (Fakultas Hukum dan Ekonomi Bisnis, 2025)
This study aims to 1) find out the socio-economic conditions of oil palm farmers in Merlung District. 2) To find out what factors influence the production of oil palm farmers in Merlung District. 3) To find out the strategy to increase oil palm production in Merlung District. The data used are primary data collected through questionnaires and direct interviews, while secondary data are obtained from related agencies. Data analysis was carried out using multiple linear regression. Based on the Rsquare value of 0.827591. This means that 82.75 percent of the variation in oil palm production is explained by the independent variables in the model, while the remaining 17.25 percent is explained by other variables outside of research, and the F test can be obtained by the value of sig = 0.000000 <0.5 this means the independent variable is land area, labor wages work, working capital and working capital simultaneously or together have a significant effect on the dependent variable, namely oil palm production. So in other words the variables of land area, labor wages, working capital and business capital are able to explain the magnitude of the dependent variable on oil palm production.